Fianna Fáil and the professionalisation of political communication in Ireland. Issue 1 (2nd January 2017) - Rafter, Kevin
ABSTRACT: The Fianna Fáil general election campaign in 1977 is widely seen as a breakthrough in political communication and election campaigning in Ireland. This 'modern' and 'professional' campaign is considered a key contest between previous campaigns and those that followed. This article, however, challenges the view that the 1977 campaign marked a key moment in terms of campaign professionalisation. Rather the argument is that the seminal moment only occurs two decades later, in 1997, with the first general election campaign of Bertie Ahern's tenure as Fianna Fáil leader. In order to assess these two campaigns, the evolution in political communication and election campaign techniques in Ireland is examined through the prism of what are labelled 'Four Ages' based on election dates: 1922–1965; 1969–1992; 1997–2011; and an emerging digital era post-2016.